Diagnóstico socioeconómico y de salud de cuatro comunidades indígenas del Municipio Huautla: un sustento para la vinculación de la carrera de Enfermería del CECyTEH. - Diana Bravo Vargas; Guillermo Nochebuena Nochebuena (Universidad de Costa Rica, 2011)
This article presents the results of a socioeconomic study and of health with the aim to possess a database of four communities near to the College of Scientific and Technological Studies of the Nobleman's State (CECyTEH). The offer was thought from the perspective of the social infirmary, the theory of the autocare and the educational entail. Methodology: The study is of exploratory and descriptive type. The theoretical method of analysis - synthesis was applied. There was applied a survey that explored two dimensions: socioeconomic and of health. There was in use the random sampling stratified with a level of reliability of 95 % and 3 % of margin of mistake and in base in the number of homes for community brought by the INEGI, 2000. With a sample of 79 selected homes. It was realized a quantitative and qualitative valuation. Result: from the survey to the communities it appeared to an indigenous population, with a high degree of vulnerability and I leave behind socially. The most frequent sufferings are the Diabetes mellitus, Hypertension and problems of the myocardium, arthritis, rheumatism and renal problems. Conclusion: a program of educational entail, produced from the perspective of the community infirmary is urgent and feasible of realizing. It is necessary that an economic offer of entail is effected, where the functions of the college have to be taken advantage by the community.